Physical Functioning, Emotional, and Behavioral Problems in Children With ADHD and Comorbid ASD: A Cross-Sectional Study. Issue 10 (August 2018) - Thomas, Simone; Sciberras, Emma; Lycett, Kate; Papadopoulos, Nicole; Rinehart, Nicole
Objective: To examine (a) physical and daily functioning in children with ADHD and autism spectrum disorder (ASD) compared with ADHD alone and (b) whether decreased physical quality of life (QoL) is associated with increased emotional and behavioral problems in children with ADHD-ASD.Method: Cross-sectional study comprising 392 children with confirmed ADHD (ADHD-ASD, n = 93; ADHD alone, n = 299) recruited from 21 pediatric practices in Victoria, Australia. Data were collected via parent and teacher surveys. Key measures included the Strengths and Difficulties Questionnaire (SDQ) and Pediatric Quality of Life Inventory (PedsQL).Results: Children with ADHD-ASD had poorer QoL across both psychosocial and physical health domains, and also had greater parent-reported behavioral, emotional, and peer problems, compared with children with ADHD alone. Poorer physical QoL partially mediated the relationship between comorbid ASD status and poorer emotional and behavioral functioning.Conclusion: The comorbid overlay of ASD in ADHD appears to influence not only problems in physical functioning but also the severity of problems relating to areas of emotional and behavioral functioning.